2017
DOI: 10.1021/acs.jmedchem.7b00355
|View full text |Cite
|
Sign up to set email alerts
|

Lipophosphonoxins II: Design, Synthesis, and Properties of Novel Broad Spectrum Antibacterial Agents

Abstract: The increase in the number of bacterial strains resistant to known antibiotics is alarming. In this study we report the synthesis of novel compounds termed Lipophosphonoxins II (LPPO II). We show that LPPO II display excellent activities against Gram-positive and -negative bacteria, including pathogens and multiresistant strains. We describe their mechanism of action-plasmatic membrane pore-forming activity selective for bacteria. Importantly, LPPO II neither damage nor cross the eukaryotic plasmatic membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 35 publications
2
47
0
Order By: Relevance
“…Kovalchuk et al (2007) showed that a complex of natural cytokines and AMPs (CCAP or Superlymph) inhibits virus proliferation in vitro. Therefore, due to their small molecular weight, good thermal stability and broad antimicrobial spectrum, AMPs are expected to replace antibiotics as new and highly effective antibacterial drugs (Presicce et al 2009;Seydlová et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Kovalchuk et al (2007) showed that a complex of natural cytokines and AMPs (CCAP or Superlymph) inhibits virus proliferation in vitro. Therefore, due to their small molecular weight, good thermal stability and broad antimicrobial spectrum, AMPs are expected to replace antibiotics as new and highly effective antibacterial drugs (Presicce et al 2009;Seydlová et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…coli polar lipid extract (Avanti Polar Lipids, Alabaster, AL, USA), or soybean lipids (Asolectin-Type II, Merck KGaA, Darmstadt, Germany). Experiments were performed as described previously 50 . The effect of colZ on peptidoglycan was tested using the dye release method described in Zhou et al .…”
Section: Methodsmentioning
confidence: 99%
“…Black lipid membrane measurements. Planar lipid membrane experiments were performed as described previously (62,63).…”
Section: Methodsmentioning
confidence: 99%